Thorn Lesions in a Modern Osteological Collection of Guanaco (Lama guanicoe): A New Paleoenviromental Proxy and Its Implications for Archaeofaunal Assemblages. (12th July 2011) - Rafuse, D. J.; Kaufmann, C. A.; Flensborg, G. A.
ABSTRACT This paper provides a detailed analysis of thorn lesions found in lower limb elements of a modern osteological collection of guanaco (Lama guanicoe). Four types of lesions were recorded: (1) thorns visible on the bone surface, (2) bony reaction with relief, (3) small negative scars and (4) medium negative scars. The methods used to recognise, record and quantify these lesions are presented. As a result, 35 of the 36 individuals analyzed contained one or more types of lesions. The highest concentrations of lesions were recorded on the anterior view of the metacarpal shafts. All the age ranges were affected by lesions; however, individuals between the ages of 1 and 3 years were the most affected, whereas those between the ages of 0 and 1 year contained the least amount of lesions. To provide examples of how thorn lesions can be identified and used as a paleoenvironmental proxy in the fossil record, we analyzed two archaeological sites from different phytogeographic provinces: Bajo de la Quinta (Monte phytogeographic province) and Calera (Pampa phytogeographic province). Results found that 25% of the elements from the Bajo de la Quinta site contained lesions, whereas none of the elements from the Calera site showed evidence of lesions. When detectable in the fossil record, thorn lesions can provide an indirect approximation of the paleoenvironment. Copyright © 2011 John Wiley & Sons, Ltd.